2004
DOI: 10.1136/oem.2003.009563
|View full text |Cite
|
Sign up to set email alerts
|

Perceived muscular tension, job strain, physical exposure, and associations with neck pain among VDU users; a prospective cohort study

Abstract: Aims: To determine whether perceived muscular tension, job strain, or physical exposure are associated with increased risk of developing neck pain among VDU users. Methods: A baseline questionnaire was answered by 1283 respondents, of whom 671 were free from neck pain at baseline. Perceived muscular tension, job strain, and physical exposure were assessed at baseline. Information about newly developed neck pain was collected in 10 follow up questionnaires and the case definition was the first report of such pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(149 citation statements)
references
References 31 publications
(28 reference statements)
7
136
0
2
Order By: Relevance
“…It is possible that this may be due to limited statistical power resulting from the small sample size in this study, although the 95% CI is narrow. Psychosocial work factors such as high job demands, low decision latitude and co-worker support, have frequently been found to be associated with increased risk of neck pain in office workers [17,19,21,27,38] as well as in some [3,30] but not all [24] studies of general working populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that this may be due to limited statistical power resulting from the small sample size in this study, although the 95% CI is narrow. Psychosocial work factors such as high job demands, low decision latitude and co-worker support, have frequently been found to be associated with increased risk of neck pain in office workers [17,19,21,27,38] as well as in some [3,30] but not all [24] studies of general working populations.…”
Section: Discussionmentioning
confidence: 99%
“…gender) [6,11,19,21] work environment factors (e.g. repetitive work, exposure level) [19,21,38] and psychosocial factors (e.g. stress, high job demands, low decision latitude) [4,6,17,21,38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have shown an association between the perception of general muscular tensio symptoms in the neck and shoulder area (Holte et al, 2003;Westgaard and De Luca, 2001). Another longitudinal study of muscle tension in the neck and shoulder area and the incidence of neck symptoms showed that high perceived muscle tension was a risk factor for the development of neck symptoms among computer users (Wahlstrom et al, 2004).…”
Section: Inmentioning
confidence: 99%
“…For instance, it has been suggested that perceived muscle tension is associated with neck and upper extremity symptoms/disorders (Wahlstrom et al, 2004). These perceived sensations may regarded as responses to biomechanical strain (e.g.…”
mentioning
confidence: 99%